Culture as an Explanation of Technology Acceptance Differences: An Empirical Investigation of Chinese and US Users - Srite, Mark (Australasian Journal of Information Systems, 2006)
This article examines the issue of the acceptance of technology across two cultures. To do this an extended technology acceptance model was tested in China and the US. Over one hundred participants, across both cultures, were surveyed as to their perceptions regarding technology acceptance. Cultural values were also measured for each group. Structural equation modeling was used to assess the research model. In general, the model explained a more than adequate amount of variance and achieved acceptable levels of significance. Differences across the two cultures were explained utilizing the cultural values of the participants. Implications for both research and practice were provided